Ghép nối động lực học hệ rôto - giá đỡ - Nguyễn, Thạc Sĩ (Bộ Giáo dục và Đào tạo, 2013)
A rotor - support system is considered as a combination of two structures: the rotor and the supporting structure. The dynamic characteristics of the rotor is represented by its dynamic flexibility matrix. Free- interface normal modes supplemented by " reduced flexibility” are used for dynamic representation of the supporting system. Finally the equations for coupling of the two substructures are developed by res to ring geometric compatibilities and force equilibrium at interfaces.